Perovskite type rare earth-based medium-entropy ceramic wave-absorbing material and preparation method thereof
By adding solid-solution rare earth elements and alkaline earth metals to the rare earth perovskite oxide absorbing materials, and preparing medium-entropy ceramic materials by using the sol-gel method, the problem of insufficient absorption performance of existing absorbing materials is solved, and the effect of efficient absorption of electromagnetic waves is achieved.
Patent Information
- Application Number
- CN202411494346.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-30
- Filing Date
- 2024-10-24
- Publication Date
- 2025-05-02
AI Technical Summary
The existing rare earth perovskite oxide absorbing materials have insufficient absorption performance, poor impedance matching, and the complex micromorphic design of composite materials is complex and costly, which limits its application development.
Perovskite rare earth-based medium-entropy ceramic material is prepared by adding solid solution rare earth elements (RE) and alkaline earth metal (AE), and prepared by sol-gel method to achieve uniform distribution of metal ions and optimization of crystal structure.
It improves the absorption capacity and dielectric loss of the material, and achieves efficient absorption of electromagnetic waves in the 2-18GHz microwave band, expands the absorption band width, has an absorption efficiency of more than 90%, and has excellent chemical stability.
Smart Images

Figure CN119912251A_ABST
Abstract
Description
[0001] This application claims priority to the following prior application: Patent application number 2023114206189 filed with the State Intellectual Property Office of China on October 30, 2023, entitled “A perovskite-type rare earth-based medium-entropy ceramic absorber material and preparation method thereof”. The entire text of the prior application is incorporated into this application by reference. Technical Field
[0002] The present invention belongs to the technical field of microwave absorbing materials, and specifically relates to a perovskite-type rare earth-based medium-entropy ceramic microwave absorbing material and a preparation method thereof, and more particularly to a perovskite-type rare earth medium-entropy AFeO 3 Wave absorbing material and preparation method thereof. Background Art
[0003] With the development of the 5G era, various production, life and scientific research activities of human beings are inseparable from the support of electromagnetic waves. However, while the use of electromagnetic waves brings convenience to people, it also brings new difficulties and challenges. In the military field, in order to improve the survivability of weapons and equipment, it is necessary to develop electromagnetic stealth technology; in the civilian field, the excessive electromagnetic waves emitted by electronic equipment when working can be harmful to the human body or interfere with other equipment. In order to eliminate the interference of electromagnetic radiation, absorbing materials are needed to play an important role.
[0004] Electromagnetic wave absorbing materials are a type of functional materials that absorb electromagnetic waves and convert them into heat energy or make electromagnetic waves disappear through interference. Ideal absorbing materials must have the characteristics of light weight, wide bandwidth, thin thickness, strong absorption capacity, adjustable absorption frequency and versatility. Rare earth perovskite oxides have a unique crystal structure, medium dielectric constant and high magnetic anisotropy, and have become a promising electromagnetic wave absorbing material. Due to the shortcomings of single-phase rare earth perovskite oxides, which have poor absorption performance and insufficient impedance matching, researchers mainly improve performance through two paradigms: material composite and structural design. However, composite materials such as carbon fiber and polymer have disadvantages such as complex micromorphology design and high price, which limit their application development. Summary of the invention
[0005] In order to improve the deficiencies of the prior art, the present invention aims to provide a perovskite rare earth based medium entropy ceramic absorbing material and a preparation method and application thereof. The present invention prepares a perovskite rare earth based medium entropy ceramic material with high absorption capacity by adding solid solution rare earth elements (RE) and alkaline earth metals (AE).
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a perovskite rare earth based medium entropy ceramic absorbing material, the chemical formula of the ceramic material is as follows: (RE1-x AE x )FeO 3 , wherein RE is selected from at least two of La, Gd, Sm, Nd, Dy, Eu, Er, and Ho, AE is selected from at least one of Ca, Sr, and Ba, 0 <x<1。
[0008] According to the present invention, in the perovskite rare earth-based medium entropy ceramic absorbing material, each metal ion is evenly distributed.
[0009] According to an embodiment of the present invention, the chemical formula of the ceramic material is (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 , (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 or (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 .
[0010] According to an embodiment of the present invention, the ceramic material has substantially Figure 1 , Figure 4 or Figure 7 XRD pattern shown.
[0011] According to an embodiment of the present invention, the ceramic material has substantially Figure 2 , Figure 5 or Figure 8 EDS diagram shown.
[0012] According to an embodiment of the present invention, the ceramic material has substantially Figure 3 , Figure 6 or Fig. 9 The reflection loss diagram is shown.
[0013] According to the embodiment of the present invention, in the ceramic material, the metal ions RE, AE, and Fe are evenly distributed on the ceramic body, thereby achieving uniform doping of the metal ions.
[0014] According to an embodiment of the present invention, the ceramic material is an orthorhombic perovskite structure, and preferably the ceramic material is a crystal structure, and the crystal belongs to the Pbnm space group.
[0015] According to an embodiment of the present invention, the unit cell structure of the crystal is a cubic structure.
[0016] According to an embodiment of the present invention, the (La 1 / 3 Nd 1 / 3 Ba1 / 3 )FeO 3 The unit cell parameters of the crystal are a=5.4846, b=5.5653, c=7.7956.
[0017] According to an embodiment of the present invention, the (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 The unit cell parameters are a=5.4908, b=5.5675, c=7.8238.
[0018] According to an embodiment of the present invention, the (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 The unit cell parameters are a=5.5164, b=5.5613, c=7.8648.
[0019] In a second aspect, the present invention further provides a method for preparing the above-mentioned perovskite rare earth-based medium entropy ceramic absorbing material, comprising the following steps:
[0020] (1) mixing iron salt, RE salt, AE salt, organic chelating agent and dispersant to carry out gelation reaction;
[0021] (2) evaporating and drying the sol to obtain a xerogel;
[0022] (3) pre-calcining the dry gel, and then grinding and calcining to obtain a medium-entropy ceramic absorbing material;
[0023] The RE and AE have the definitions as described above.
[0024] According to an embodiment of the present invention, the iron salt is selected from at least one of iron nitrate, iron sulfate, iron chlorate or corresponding hydrated salts, such as iron nitrate nonahydrate.
[0025] According to an embodiment of the present invention, the RE salt is selected from at least one of nitrates, sulfates, chlorates or corresponding hydrated salts of RE, for example, selected from lanthanum nitrate, gadolinium nitrate, and samarium nitrate.
[0026] According to an embodiment of the present invention, the barium salt is selected from at least one of nitrate, sulfate, chlorate or corresponding hydrate of AE, such as calcium nitrate.
[0027] According to an embodiment of the present invention, the organic chelating agent is selected from at least one of citric acid, citric acid monohydrate or oxalic acid.
[0028] According to an embodiment of the present invention, the dispersant is selected from at least one of ethylene glycol, propylene glycol, butylene glycol, and polyethylene glycol, for example, ethylene glycol.
[0029] According to an embodiment of the present invention, the molar ratio of the total molar amount of metal ions to the chelating agent in step (1) is 1:(0.6-5), preferably the molar ratio of the total molar amount of metal ions to the chelating agent is 1:(1-4), for example, 1:1, 1:1.2, 1:1.5, 1:2, 1:3, 1:4.
[0030] According to an embodiment of the present invention, the mass ratio of the chelating agent to the dispersant in the step (1) is 1:(0.6-5), preferably the mass ratio of the chelating agent to the dispersant is 1:(1-3), for example, 1:1, 1:1.2, 1:3, 1:4.
[0031] According to an embodiment of the present invention, the temperature of the gelation reaction in step (1) is 70-120°C, preferably the temperature of the gelation reaction is 70-100°C, and further preferably, the temperature of the gelation reaction is 70-90°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C.
[0032] According to an embodiment of the present invention, the gelation reaction time in step (1) is 1-12 hours, preferably the gelation reaction time is 2-8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours.
[0033] According to an embodiment of the present invention, the gelation reaction in step (1) is carried out under stirring conditions, and the stirring speed is 300-800 r / min, for example, 500 r / min.
[0034] According to an embodiment of the present invention, the drying temperature in step (2) is 60-120°C, preferably the drying temperature is 70-100°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C.
[0035] According to an embodiment of the present invention, the drying time in step (2) is 2-24 hours, preferably the drying time is 6-15 hours, such as 3 hours, 6 hours, 12 hours.
[0036] According to an embodiment of the present invention, the pre-firing temperature in step (3) is 200-600°C, preferably the pre-firing temperature is 300-500°C, for example 500°C.
[0037] According to an embodiment of the present invention, the pre-burning time in step (3) is 1-5 hours, preferably the pre-burning time is 2-4 hours, such as 2 hours.
[0038] According to an embodiment of the present invention, the heating rate of the pre-calcination in step (3) is 1-10°C / min, preferably the heating rate of the pre-calcination is 3-7°C / min, such as 5°C / min.
[0039] According to an embodiment of the present invention, the calcination temperature in step (3) is 800-1300°C, preferably the calcination temperature is 900-1100°C, for example 1000°C.
[0040] According to an embodiment of the present invention, the calcination time in step (3) is 4-10 hours, preferably the calcination time is 5-9 hours, such as 8 hours.
[0041] According to an embodiment of the present invention, the heating rate of the calcination in step (3) is 1-10°C / min, and preferably the heating rate of the pre-calcination is 3-7°C / min, such as 5°C / min.
[0042] In a third aspect, the present invention provides an absorbing material composition, which comprises the perovskite rare earth-based medium-entropy ceramic absorbing material as described above and an additive.
[0043] According to an embodiment of the present invention, the auxiliary agent includes paraffin.
[0044] Beneficial Effects
[0045] 1) The invention introduces the design paradigm of medium entropy, which provides a direction for the composition design and performance regulation of materials. According to literature research, medium entropy ceramics have the same characteristics of four major effects as high entropy ceramics (HECs), which brings them many excellent properties. The characteristics of high entropy ceramics can be summarized as four points: (1) Thermodynamic high entropy effect; (2) Structural lattice distortion effect; (3) Dynamic hysteresis diffusion effect; (4) Performance "cocktail" effect. One of the core effects of the material is slow diffusion, and the lattice distortion caused by the solid solution and the coordinated diffusion of multiple elements hinder the movement of atoms and the effective diffusion of atoms, which points out the way forward for the performance regulation in the field of wave absorption.
[0046] 2) The present invention adopts the sol-gel method to prepare the perovskite rare earth-based medium entropy ceramic absorbing material, and the synthesized grains are small and uniform. The present invention can obtain the absorbing material through gelation reaction, pre-sintering and calcining, and the preparation process is simple and suitable for large-scale production. The perovskite rare earth-based medium entropy ceramic absorbing material prepared by the present invention, on the one hand, due to the introduction of alkaline earth metals, a variety of polarizations are generated, including space charge polarization, dipole polarization and interface polarization, which enhances the dielectric loss of the material; on the other hand, by doping different rare earth elements, the lattice distortion effect and "cocktail effect" of entropy in the application make the perovskite system medium / high entropy ceramic absorbing material have strong absorption capacity and different absorption properties in different frequency bands. In addition, the perovskite rare earth-based medium entropy ceramic absorbing material has excellent chemical stability.
[0047] 3) The absorbing material provided by the present invention can absorb electromagnetic waves in the microwave band of 2-18 GHz, has a wide absorption frequency band (the frequency band of existing oxides with R<-10dB is generally <2 GHz), has high absorption efficiency (>90%), and has good thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The perovskite rare earth-based medium entropy ceramic absorbing powder material (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 XRD pattern of
[0049] Figure 2 (La prepared in Example 1 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 Transmission EDS element distribution diagram of ceramic absorbing powder material;
[0050] Figure 3 (La prepared in Example 1 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 Reflection loss diagram of ceramic absorbing powder material;
[0051] Figure 4 The perovskite rare earth-based medium entropy ceramic absorbing powder material (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 XRD pattern of
[0052] Figure 5 (La prepared in Example 21 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 Transmission EDS element distribution diagram of ceramic absorbing powder material;
[0053] Figure 6 (La prepared in Example 1 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 Reflection loss diagram of ceramic absorbing powder material;
[0054] Figure 7 The perovskite rare earth-based medium / high entropy ceramic absorbing powder material (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 XRD pattern of
[0055] Figure 8 (La prepared in Example 3 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 Transmission EDS element distribution diagram of ceramic absorbing powder material;
[0056] Fig. 9 (La prepared in Example 3 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 Reflection loss diagram of ceramic microwave absorbing powder material. DETAILED DESCRIPTION
[0057] The following will further describe the absorbing material of the present invention, its preparation method and application in combination with specific embodiments. It should be understood that the following embodiments are only for illustrative purposes and explanation of the present invention, and should not be interpreted as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope of protection of the present invention.
[0058] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0059] The method for calculating the reflection loss of the ceramic b-wave absorbing material prepared in Examples 1-3 is as follows:
[0060] The powder (ceramic absorbing material prepared in Example 1-3) and paraffin wax were mixed in a ratio of 4:1 (mass ratio) to prepare a coaxial sample with an outer diameter of 7 mm and an inner diameter of 3.04 nm, respectively. The complex magnetic permeability and complex dielectric constant of the sample in the frequency band of 2-18 GHz were measured by a vector network analyzer of Siyi, and then the reflection loss RL of the single-layer absorbing material was calculated and simulated by the following formula:
[0061]
[0062] In the formula, ε r , μ r and d are the relative dielectric constant, relative magnetic permeability and thickness of the absorbing material, respectively, f is the frequency of the electromagnetic wave, c is the propagation speed of the electromagnetic wave in free space (i.e., the speed of light), and j is an imaginary unit.
[0063] Example 1 A rare earth perovskite-based medium entropy (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 A method for preparing a ceramic microwave absorbing powder material, the method comprising the following steps:
[0064] (1) Weigh 0.01 mol of La(NO 3 ) 3 6H 2 O.Gd(NO 3 ) 3 6H 2 O、Ba(NO 3 ) 2 , 0.03 mol of Fe(NO 3 ) 3 9H 2 O was dissolved in 200 mL of distilled water to obtain a solution, and then 0.072 mol of citric acid was weighed according to the molar ratio of total metal ions (lanthanum ions, gadolinium ions, barium ions and iron ions) to citric acid of 1:1.2, and added to the above solution. The purpose of adding citric acid is to ensure that citric acid can bind to all metal ions; at the same time, ethylene glycol was added as a dispersant, and the mass ratio of citric acid to ethylene glycol was 1:1.2 to obtain a mixed solution, and the obtained mixed solution was placed in a water bath, and constant temperature magnetic stirring was continued at 80°C (stirring speed was 500r / min), and gelation reaction was carried out for 3 hours to obtain a gel;
[0065] (2) placing the gel obtained in step (1) in a forced air drying oven and drying at 80° C. for 10 h to obtain a dry gel;
[0066] (3) The dry gel obtained in step (2) was pre-calcined at 400° C. for 3 h, and the obtained material was ground and placed in a muffle furnace for calcination at 900° C. for 4 h to obtain a medium-entropy rare earth-based ceramic absorbing powder material (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 .
[0067] The perovskite rare earth based medium entropy ceramic absorbing material (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 XRD test was performed, and the test results were as follows Figure 1 As shown, from Figure 1 It can be seen from the figure that the prepared sample has an orthorhombic perovskite structure, no extra impurity peaks appear, and the product has a complete crystal form. 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 The unit cell parameters are a=5.5164, b=5.5613, c=7.8648, which are consistent with the perovskite structure.
[0068] Figure 2 The perovskite rare earth based medium entropy ceramic absorbing powder material (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 From the EDS (energy dispersive spectrometer) image of the transmission electron microscope (TEM), we can see that La, Gd, Ba, and Fe metal ions are evenly distributed on the ceramic body, achieving uniform doping of metal ions.
[0069] The medium entropy rare earth-based ceramic absorbing powder material (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3 Performing a return loss test Figure 3 This is the reflection loss diagram of the absorbing powder material prepared in Example 1 at 2.2 mm. Figure 3 It can be seen that (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO 3The minimum reflection loss frequency is 10.56 GHz, the minimum reflection loss peak reaches -48.18 dB, and the maximum effective frequency band (below -10 dB) width reaches 5.18 GHz, indicating that the microwave absorbing material prepared in this example has excellent microwave absorption performance in the mid-frequency region.
[0070] Example 2 A rare earth perovskite-based medium entropy (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 A method for preparing a ceramic microwave absorbing powder material, the method comprising the following steps:
[0071] (1) Weigh 0.01 mol of La(NO 3 ) 3 6H 2 O、Sm(NO 3 ) 3 6H 2 O、Ba(NO 3 ) 2 , 0.03 mol of Fe(NO 3 ) 3 9H 2 O and dissolve it in 200mL of distilled water to obtain a dissolving solution, and then weigh 0.072mol of citric acid according to the molar ratio of total metal ions (lanthanum ions, samarium ions, barium ions and iron ions) to citric acid of 1:1.2, and add it to the above dissolving solution to ensure that citric acid can bind to all metal ions; at the same time, add ethylene glycol as a dispersant, and feed according to the mass ratio of citric acid to ethylene glycol of 1:1.2 to obtain a mixed solution, put the obtained mixed solution into a water bath, and continue constant temperature magnetic stirring (stirring speed of 500r / min) at 80°C, and perform gelation reaction for 3-4h to obtain a gel;
[0072] (2) placing the gel obtained in step (1) in a forced air drying oven at 100° C. for 8 h to obtain a dry gel;
[0073] (3) The dry gel obtained in step (2) was pre-calcined at 500° C. for 2 h, and the obtained material was ground and placed in a muffle furnace for calcination at 1000° C. for 10 h to obtain a medium-entropy rare earth-based ceramic absorbing powder material (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 .
[0074] The perovskite rare earth based medium entropy ceramic absorbing material (La 1 / 3 Sm 1 / 3 Ba1 / 3 )FeO 3 XRD test was performed, and the test results were as follows Figure 4 As shown, the ceramic absorbing powder material prepared in this embodiment has an orthorhombic perovskite structure, which is consistent with the peak shape of the ceramic absorbing powder material prepared in Example 1, without any extra impurity peaks, and the product has a complete crystal form. 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 The unit cell parameters are a=5.4908, b=5.5675, c=7.8238, which are consistent with the perovskite structure.
[0075] Figure 5 The perovskite rare earth based medium entropy ceramic absorbing powder material (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 The EDS image of the transmission electron microscope (TEM) shows that the La, Sm, Ba, and Fe metal ions are evenly distributed on the ceramic body, achieving uniform doping of metal ions.
[0076] Figure 6 The perovskite rare earth based medium entropy ceramic absorbing powder material (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 The reflection loss test is shown in the figure, which shows the reflection loss curve of the absorbing powder material prepared in this embodiment at 2.0 mm. Figure 6 It can be seen that (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO 3 The minimum reflection loss frequency is 11.12 GHz, the minimum reflection loss peak reaches -56.81 dB, and the maximum effective frequency band (below -10 dB) width reaches 5.02 GHz, indicating that the microwave absorbing material prepared in the example has excellent microwave absorption performance in the mid-frequency region.
[0077] Example 3 A rare earth perovskite-based medium entropy (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 A method for preparing a ceramic microwave absorbing powder material, the method comprising the following steps:
[0078] (1) Weigh 0.01 mol of La(NO 3 ) 3 6H 2 O、Nd(NO 3) 3 6H 2 O、Ba(NO 3 ) 2 , 0.03 mol of Fe(NO 3 ) 3 9H 2 O and dissolve it in 200mL of distilled water to obtain a dissolving solution, and then weigh 0.072mol of citric acid according to the molar ratio of metal ions (lanthanum ions, neodymium ions, barium ions and iron ions) to citric acid of 1:1.2, and add it to the above dissolving solution to ensure that citric acid can bind to all metal ions; at the same time, add ethylene glycol as a dispersant, and feed according to the mass ratio of citric acid to ethylene glycol of 1:1.2 to obtain a mixed solution, put the obtained mixed solution into a water bath, and continue constant temperature magnetic stirring (stirring speed is 500r / min) at 80°C, and perform gelation reaction for 3-4h to obtain a gel;
[0079] (2) placing the gel obtained in step (1) in a forced air drying oven at 120° C. for 6 h to obtain a dry gel;
[0080] (3) The dry gel obtained in step (2) was pre-calcined at 600° C. for 2 h, and the obtained material was ground and placed in a muffle furnace for calcination at 1100° C. for 4 h to obtain a medium-entropy rare earth-based ceramic absorbing powder material (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 .
[0081] The perovskite rare earth based medium entropy ceramic absorbing material (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 XRD test was performed, and the test results were as follows Figure 7 Therefore, the absorbing powder material prepared in this example has an orthorhombic perovskite structure and belongs to the Pbnm space group. The peak shape of the absorbing powder material of the samples prepared in Example 1 and Example 2 is consistent, no extra impurity peaks appear, and the product crystal form is complete. 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 The unit cell parameters are a=5.4846, b=5.5653, c=7.7956, which are consistent with the perovskite structure.
[0082] Figure 8 The perovskite rare earth based medium entropy ceramic absorbing powder material (La 1 / 3 Nd 1 / 3 Ba1 / 3 )FeO 3 The EDS image of the transmission electron microscope (TEM) shows that La, Nd, Ba, and Fe metal ions are evenly distributed on the ceramic body, achieving uniform doping of metal ions.
[0083] Fig. 9 Perovskite rare earth based medium entropy ceramic microwave absorbing powder material (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 The reflection loss test shows the reflection loss curve of the absorbing powder prepared in this embodiment at 2.0 mm. (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO 3 The minimum reflection loss frequency is 11.12 GHz, the minimum reflection loss peak reaches -56.35 dB, and the maximum effective frequency band (below -10 dB) width reaches 4.46 GHz, indicating that the microwave absorption material of this embodiment has excellent microwave absorption performance in the mid-frequency region.
[0084] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A perovskite rare earth based medium entropy ceramic absorbing material, characterized in that: The chemical formula of the ceramic material is as follows: (RE 1-x AE x )FeO3, wherein RE is selected from at least two of La, Gd, Sm, Nd, Dy, Eu, Er, and Ho, AE is selected from at least one of Ca, Sr, and Ba, 0 <x<1。 Preferably, in the perovskite rare earth-based medium entropy ceramic absorbing material, the various metal ions are evenly distributed, and in the ceramic material, the metal ions RE, AE, and Fe are evenly distributed on the ceramic body, thereby achieving uniform doping of the metal ions.
2. The perovskite rare earth based medium entropy ceramic absorbing material according to claim 1, characterized in that: The chemical formula of the ceramic material is (La 1 / 3 G 1 / 3 Ba 1 / 3 )FeO3、(La 1 / 3 Sm 1 / 3 Ba 1 / 3 )FeO3 or (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )FeO3. Preferably, the ceramic material has an XRD pattern as shown in FIG. 1 , FIG. 4 or FIG. 7 . Preferably, the ceramic material has an EDS graph as shown in FIG. 2 , FIG. 5 or FIG. 8 . Preferably, the ceramic material has a reflection loss diagram as shown in FIG. 3 , FIG. 6 or FIG. 9 .
3. The perovskite rare earth based medium entropy ceramic absorbing material according to claim 1 or 2, characterized in that: The ceramic material is an orthorhombic perovskite structure. Preferably, the ceramic material is a crystal structure. The crystal belongs to the Pbnm space group, and the unit cell structure of the crystal is a cubic structure. For example, the (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )The unit cell parameters of FeO3 crystal are a=5.4846, b=5.5653, c=7.7956. For example, the (La 1 / 3 Nd 1 / 3 Ba 1 / 3 )The unit cell parameters of FeO3 crystal are a=5.4846, b=5.5653, c=7.7956. For example, the (La 1 / 3 Sm 1 / 3 Ba 1 / 3 )The unit cell parameters of FeO3 are a=5.4908, b=5.5675, c=7.8238. According to an embodiment of the present invention, the (La 1 / 3 G 1 / 3 Ba 1 / 3 )The unit cell parameters of FeO3 are a=5.5164, b=5.5613, c=7.8648.
4. A method for preparing the perovskite rare earth-based medium entropy ceramic absorbing material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing iron salt, RE salt, AE salt, organic chelating agent and dispersant to carry out gelation reaction; (2) evaporating and drying the sol to obtain a xerogel; (3) The dry gel is pre-sintered, then ground and calcined to obtain a medium-entropy ceramic absorbing material.
5. The preparation method according to claim 4, characterized in that: The iron salt is selected from at least one of iron nitrate, sulfate, chlorate or corresponding hydrated salts; The RE salt is selected from at least one of nitrate, sulfate, chlorate or corresponding hydrated salts of RE; The barium salt is selected from at least one of nitrate, sulfate, chlorate or corresponding hydrate of AE; The organic chelating agent is selected from at least one of citric acid, citric acid monohydrate or oxalic acid; The dispersant is selected from at least one of ethylene glycol, propylene glycol, butylene glycol and polyethylene glycol.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the total molar amount of metal ions to the chelating agent in the step (1) is 1:(0.6-5); the mass ratio of the chelating agent to the dispersant in the step (1) is 1:(0.6-5).
7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the gelation reaction in step (1) is 70-120° C., and the time of the gelation reaction is 1-12 hours; Preferably, the drying temperature in step (2) is 60-120° C., and the drying time is 2-24 h.
8. The preparation method according to any one of claims 4 to 6, characterized in that: The pre-burning temperature in step (3) is 200-600° C., and the pre-burning time is 1-5 hours.
9. The preparation method according to any one of claims 4 to 6, characterized in that: In the step (3), the calcination temperature is 800-1300° C., and the calcination time is 4-10 hours.
10. A wave absorbing material composition, characterized in that: The absorbing material composition comprises the perovskite rare earth based medium entropy ceramic absorbing material according to any one of claims 1 to 3 or the perovskite rare earth based medium entropy ceramic absorbing material prepared by the method according to any one of claims 4 to 9.
Citation Information
Patent Citations
BaLaFeO wave-absorbing material and preparation method thereof
CN110550944A
LaCaFeO wave-absorbing material and preparation method thereof
CN115784317A
SmCaFeO wave-absorbing material and preparation method thereof
CN116395750A
High-temperature dielectric wave-absorbing ceramic and preparation method thereof
CN116813319A
MOF-derived multi-element rare earth-based composite wave-absorbing material and preparation method thereof
CN116944494A
Cited By
A Ce-doped erbium ferrite material, its preparation method and application
CN122575900A